Оптимальні оцінки імпульсної дії в задачі практичної стійкості диференціальних включень з імпульсним впливом - Linder, Ia. M.; Pichkur, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
The practical stability of differential inclusions with multivalued impulse impact is studied. The properties of optimal estimations of impulse function for systems with impulse impact are justified: for nonlinear differential inclusions the optimality criterion of impulse estimate is proved. In the case of linear differential inclusion with linear impulse impact which satisfies separation condition, the analytical expression for the evaluation of the optimal impulse, which provides practical stability of the system at a given time interval is obtained. The results are algorithmic oriented.